Exploring Lebanon's Growth Prospects - World Bank (Washington, DC, 2013)
This policy note reviews the current determinants of gross domestic product growth in Lebanon, and proposes a strategy to accelerate such growth in the years to come. Emigration and macro-economic trends will require urgent attention to foster growth. In the absence of job opportunities, half of each Lebanese generation eventually emigrates while another fourth stays idle. Lebanon's active population is aging, its human capital is eroding, and its resident population is aging. To reverse these trends, growth needs to be accelerated to meet Lebanese economic expectations. Reviewing various possible constraints, the note concludes that fiscal imbalances and barriers to entry are most binding to economic growth. A pro-growth strategy could be articulated around fiscal stabilization and reducing barriers to investment. If synonymous with structural reforms in the pension, civil service and energy sectors, fiscal stabilization could even bring significant growth rewards, which are estimated at 0.4-0.5 percentage points of additional real GDP growth per year.